1998
DOI: 10.1001/archinte.158.5.491
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of AIDS-Defining Illnesses in 4883 Patients With Human Immunodeficiency Virus Infection

Abstract: This study provides important information about the risk of AIDS-defining illnesses at lower CD4 lymphocyte counts, enabling disease-specific prophylaxis to be targeted at the most appropriate population. In the future, as more prophylactic therapies are developed, this study will provide historical data of the incidence of diseases before specific prophylaxis was introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 39 publications
1
35
2
Order By: Relevance
“…The incidence of KS in AIDS patients is 20,000 times higher versus 300 times higher in immunosuppressive patients than it is in the general population (7). Second, KS frequently has early presentation prior to the onset of severe immunosuppression in patients with AIDS (8). Moreover, KS is rapidly regressed in patients undergoing triple antiretroviral therapy before the complete restoration of the immune system (5).…”
mentioning
confidence: 99%
“…The incidence of KS in AIDS patients is 20,000 times higher versus 300 times higher in immunosuppressive patients than it is in the general population (7). Second, KS frequently has early presentation prior to the onset of severe immunosuppression in patients with AIDS (8). Moreover, KS is rapidly regressed in patients undergoing triple antiretroviral therapy before the complete restoration of the immune system (5).…”
mentioning
confidence: 99%
“…While HIV-1 infection alone is not sufficient for the development of Kaposi's sarcoma, AIDS-associated Kaposi's sarcoma is more aggressive, disseminated, and resistant to treatment than the other forms, including posttransplant Kaposi's sarcoma (10,37,86). Immunosuppression alone cannot explain the much greater prevalence of Kaposi's sarcoma in AIDS patients than in other immunosuppressed individuals, the frequent presentation of Kaposi's sarcoma prior to immunosuppression in HIV-infected individuals, and the association of Kaposi's sarcoma with HIV-1 but not HIV-2 infection in West Africa (2,5,64,75). Thus, there has been much interest in HIV-related factors that might potentiate the development of Kaposi's sarcoma.…”
mentioning
confidence: 99%
“…Until the date of the end of this study, a low absolute CD4+ lymphocyte count remains a major, independent risk factor for the development of major opportunistic infections (including visceral-disseminated candidiasis), while a preexisting oropharyngeal candidiasis is the more obvious source of an esophageal extension of disease [1,11,19,20], although this last issue is not always retrieved in all patients suffering from esophageal candidiasis [8]. In fact, a number of cohort studies, either prospective or retrospective in nature, confirmed the elevated incidence of visceral candidiasis among immunocompromised HIV-infected patients, and its strict relationship with the peripheral CD4+ lymphocyte count, with a threshold usually placed at 200 cells/μL [1,3,4,11].…”
Section: Discussionmentioning
confidence: 95%
“…In the era of highly active antiretroviral therapy (HAART) a dramatic drop of immunodeficiency-related opportunism occurred (especially for disorders associated with a CD4+ lymphocyte count below 50-100 cells/μL, like cryptosporidiosis, cytomegalovirosis, atypical mycobacteriosis, isosporiasis, neurotoxoplasmosis, and cryptococcosis) [1][2][3][4][5], compared with the years preceding the introduction of potent antiretroviral combinations (before mid-1996) [6][7][8]. However, in the HAART era the distribution of the main AIDS-defining diseases remained somewhat unchanged in their respective proportion [1][2][3][4]9].…”
mentioning
confidence: 99%
See 1 more Smart Citation